Cultural Consensus About Happiness Among the Elderly - Aguilera-Velasco, MarÃa de los Ãngeles; Acosta-FernÃ¡ndez, MartÃn; Franco-ChÃ¡vez, Sergio Adalberto; Soltero-Avelar, RubÃ©n (European Scientific Journal, ESJ, 2017)
The purpose of this study was to analyze cultural consensus about happiness among the elderly by identifying meanings and conceptual dimensions of the concept. A qualitative study was made with an exploratory descriptive design in two successive phases, with free list and pile sorting by a non-random purposive sampling of 76 elderly adults with an average age of 65.35. The results evidenced cultural consensus in the two conceptual models of happiness, one for men and another for women, with high concordance in individual and group answers. The models consisted of two conceptual dimensions of happiness: economic stability and support. The models show limited happiness due to constant concerns of having employment and money to eat, live and buy medicine, which they can overcome thanks to the family support net. Specifically, men were more concerned about economic support for household expenses and for helping their siblings. On the other hand, women had a vision more focused on themselves and on their religious beliefs. The cultural meaning of happiness for women included children and tranquility while for men it meant health, children, wellbeing and family. The conclusion is that the elderly we studied are aware of the importance of their happiness and how to reach it. The looming limiting factor was being excluded from Social Security benefits and not having money or government support. We recommend the State lend support to these people with medical care and free medicine, offer sufficient stable economic support after their 60th birthday, and promote knowledge and experiences to women beyond religious beliefs as well as the practices of laughter and peace among men for the purpose of widening their expectations by traveling, enjoying themselves and with leisure and recreational activities.